Fabrication and characteristics of high‐power multijunction LEDs using GaN‐on‐Si technologies. Issue 5 (9th March 2016) - Tajima, Jumpei; Ono, Hiroshi; Ito, Toshihide; Uesugi, Kenjiro; Nunoue, Shinya
Abstract : GaN‐based multijunction light‐emitting diodes (MJ‐LEDs) capable of operating at high voltage and high power were fabricated. The device structure of the MJ‐LEDs was based on a thin‐film flip‐chip LED and consisted of several junctions connected in series. High‐voltage operation and uniform electroluminescence were achieved in the MJ‐LEDs whose chip size was from 1.5 to 2.5‐mm‐square. Under a driving power of 5.8 W, the light output power of a 12‐junction LED was over 3.1 W with encapsulation. A white lamp based on the MJ‐LED and a YAG:Ce phosphor exhibited a luminous efficacy of 111 lm W −1 in 6.1 W operations when the stage temperature was 85 °C.